Fidelity of RNA polymerase II transcription controlled by elongation factor TFIIS - Jeon, ChoonJu (The National Academy of Sciences of the USA, 1996)
Fidelity of DNA and protein synthesis is regulated by a proofreading mechanism but function of a similar mechanism during RNA synthesis has not been demonstrated. Analysis of transcriptional fidelity and its control has been hampered by the necessity to employ complex DNA templates requiring either a promoter and initiation factors or 3′-extended templates. To circumvent this difficulty, we have created an RNA–DNA dumbbell template that can be recognized as a template-primer and extended by RNA polymerase II. By employing this system, we demonstrate that RNA polymerase II can misincorporate a nucleotide and carry out template-dependent elongation at the mispaired end. The transcripts containing misincorporated residues can be cleaved by the very slow 3′ → 5′ ribonuclease activity of the RNA polymerase II, but enhancement of this activity by the elongation factor TFIIS generates RNA with a high degree of fidelity. This enhanced preferential cleavage of misincorporated transcripts suggests an important role for TFIIS in maintaining transcriptional fidelity.